Raloxifene modulates regulators of osteoclastogenesis and angiogenesis in an oestrogen deficiency periapical lesion model - Gomes Filho, João Eduardo [UNESP]; Wayama, Marcelo Tadahiro; Dornelles, R. C. M.; Ervolino, Edilson [UNESP]; Yamanari, Guilherme Hiroshi; Lodi, C. S.; Araújo, Gustavo Sivieri de [UNESP]; Dezan Junior, Eloi [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (Wiley, 2014)
Aim To analyse the local regulatory mechanisms of osteoclastogenesis and angiogenesis during the progression of periapical lesions in female rats with oestrogen deficiency and treatment with raloxifene (RLX). Methodology Female Wistar rats were distributed into groups: SHAM-veh, subjected to sham surgery and treated with a vehicle; OVX-veh, subjected to ovary removal and treated with a vehicle; and OVX-RLX, subjected to ovary removal and treated with RLX. Vehicle or RLX was administered orally for 90 days. During treatment, the dental pulp of mandibular first molars was exposed to the oral environment for induction of periapical lesions, which were analysed after 7 and 30 days. After the experimental periods, blood samples were collected for measurement of oestradiol, calcium, phosphorus and alkaline phosphatase. The rats were euthanized and the mandibles removed and processed for immunohistochemical detection of receptor activator of nuclear factor kappa-B ligand (RANKL), osteoprotegerin (OPG), hypoxia-inducible factor-1 alpha (HIF-1α) and bone-specific alkaline phosphatase (BALP). Data were compared using Kruskal–Wallis followed by Dunn test (nonparametric values) and anova followed by the Tukey's test (parametric values). Results The plasma concentration of oestradiol showed hypo-oestrogenism in the rats subjected to ovary removal. On day 7, alkaline phosphatase activity, calcium and phosphorus were higher in the OVX-RLX group than in the OVX-veh group (P < 0.001), but immunolabelling for RANKL and HIF-1α was lower in OVX-RLX group (P < 0.001). On day 30, the OVX-veh group had higher immunolabelling for RANKL than the OVX-RLX group (P < 0.05). There were no significant differences in the immunoreactivity of OPG and BALP between any groups at either time-point (P > 0.05). Conclusion RLX therapy reversed the increased levels of the local regulators of both osteoclastogenesis and angiogenesis induced by oestrogen deficiency.
Keywords: Bone metabolism; Ovariectomized; Periapical lesion; Raloxifene hydrochloride